2009
DOI: 10.1007/s00427-009-0312-x
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionarily conserved Myostatin proximal promoter/enhancer confers basal levels of transcription and spatial specificity in vivo

Abstract: Myostatin (Mstn) is a negative regulator of skeletal muscle mass, and Mstn mutations are responsible for the double muscling phenotype observed in many animal species. Moreover, Mstn is a positive regulator of adult muscle stem cell (satellite cell) quiescence, and hence, Mstn is being targeted in therapeutic approaches to muscle diseases. In order to better understand the mechanisms underlying Mstn regulation, we searched for the gene's proximal enhancer and promoter elements, using an evolutionary approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
14

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 51 publications
2
17
0
14
Order By: Relevance
“…Although Malat1 is known to be capable of regulating tumor development and metastasis, this is the first time it has been characterized in skeletal muscle, let alone implicated in skeletal myogenesis. Althought the mechanisms by which myostatin regulates the expression of Malat1 and by which Malat1 regulates Cdk6 and myogenin expression still need to be elucidated, both Malat1 and myostatin contain a cAMP-response elements in their proximal promoter as do many myogenic genes (7,17). This suggests that myostatin and Malat1 may be regulated by a common signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although Malat1 is known to be capable of regulating tumor development and metastasis, this is the first time it has been characterized in skeletal muscle, let alone implicated in skeletal myogenesis. Althought the mechanisms by which myostatin regulates the expression of Malat1 and by which Malat1 regulates Cdk6 and myogenin expression still need to be elucidated, both Malat1 and myostatin contain a cAMP-response elements in their proximal promoter as do many myogenic genes (7,17). This suggests that myostatin and Malat1 may be regulated by a common signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Meis1 and Pknox2 are members of a small family of transcription factors that function in skeletal muscle as pioneer transcription factors to stabilize the MyoD/E12 DNA interaction on suboptimal E box sites, such as the E box found on the myogenin promoter (32)(33)(34). Although little is known about the function of Pknox2, it is similar in homology to Meis1 and is highly expressed in skeletal muscle tissue (35).…”
Section: Mef2amentioning
confidence: 99%
“…However, few studies have reported on the characterization of the promoter which exhibits more divergence across the species (5)(6)(7). The level of conservation of several regulatory motifs in MSTN promoter among different species is not known to a greater extent (8).…”
Section: Introductionmentioning
confidence: 99%